High School Sudents’ Perceptions of The Role of Instagram Content on Vocabulary Mastery - Mu’Minin, Sholikhatul; Agustina, Sheila (PROJECT (Professional Journal of English Education), 2025)
Nowadays, English language learning has been transformed along with the development of technology. This causes the use of Instagram as a learning media, especially to improve vocabulary. This study aims to determine students’ perceptions of the role Instagram content on vocabulary mastery. The data were analyzed using qualitative descriptive methodology. The respondents of this study were 34 students who use Instagram to learn vocabulary. To get more in-depth information, the researchers also conducted interviews with 5 informants. The findings show that Instagram content is an effective tool to help students improve their English vocabulary. Interaction with various features on Instagram such as reels, quizzes, posts, and stories available also makes learning more interesting and indirectly encourages them to be actively involved. Future research recommendation could curate relevant Instagram content for vocabulary learning and integrate it into classroom learning activities, highlighting the need for a more comprehensive approach.